l-Borneol Exerted the Neuroprotective Effect by Promoting Angiogenesis Coupled With Neurogenesis via Ang1-VEGF-BDNF Pathway - Ma, Rong; Xie, Qian; Li, Hongyan; Guo, Xiaoqing; Wang, Jian; Li, Yong; Ren, Mihong; Gong, Daoyin; Gao, Tian (Frontiers in Pharmacology, 2021)
At present, Stroke is still one of the leading causes of population death worldwide and leads to disability. Traditional Chinese medicine plays an important role in the prevention or treatment of stroke. l-borneol, a traditional Chinese medicine, has been used in China to treat stroke for thousands of years. However, its mechanism of action is unclear. After cerebral ischemia, promoting angiogenesis after cerebral ischemia and providing nutrition for the infarct area is an important strategy to improve the damage in the ischemic area, but it is also essential to promote neurogenesis and replenish new neurons. Here, our research shows that l-borneol can significantly improve the neurological deficits of pMCAO model rats, reduce cerebral infarction, and improve the pathological damage of cerebral ischemia. and significantly increase serum level of Ang-1 and VEGF, and significantly decrease level of ACE and Tie2 to promote angiogenesis. PCR and WB showed the same results. Immunohistochemistry also showed that l-borneol can increase the number of CD34 positive cells, further verifying that l-borneol can play a neuroprotective effect by promoting angiogenesis after cerebral ischemia injury. In addition, l-borneol can significantly promote the expression level of VEGF, BDNF and inhibit the expression levels of TGF-β1 and MMP9 to promote neurogenesis. The above suggests that l-borneol can promote angiogenesis coupled neurogenesis by regulating Ang1-VEGF-BDNF to play a neuroprotective effect. Molecular docking also shows that l-borneol has a very high binding rate with the above target, which further confirmed the target of l-borneol to improve cerebral ischemic injury. These results provide strong evidence for the treatment of cerebral ischemia with l-borneol and provide reference for future research.